Peristaltic activity of blood–titanium nanofluid subject to endoscope and entropy generation - Hayat, Tasawar; Nawaz, Sadaf; Alsaedi, Ahmed; Ahmad, Bashir (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2018)
Entropy generation and endoscopic effects on peristalsis of nanofluid are addressed. Inner tube is taken rigid, while sinusoidal wave travels along the outer tube. Blood is used as the base fluid, whereas titanium is considered as nanoparticle. Maxwell model of effective thermal conductivity is utilized. Velocity and thermal slip conditions are imposed at outer tube. Moreover, the walls of tubes are complaint in nature. Viscous dissipation is also utilized. Long wavelength and small Reynolds number consideration is employed. Series solutions are obtained for small Grashof number. Analysis is carried out for physical parameters on velocity, temperature, entropy generation and Bejan number. Heat transfer rate at wall is also analyzed via bar charts for different pertinent parameters. Results reveal that an enhancement in nanomaterial volume fraction causes decay in temperature and velocity, whereas it leads to increase the heat transfer rate at the wall. Grashof number causes an enhancement in velocity and temperature. The study also declared that elastance coefficients of walls lead to enhancement, whereas damping coefficient results in decay of velocity, temperature and entropy generation.